Pemanfaatan Teknologi Cloud Computing untuk Kolaborasi Pembelajaran Matematika di Lingkungan Sekolah (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This study aims to evaluate the utilization of cloud computing technology in supporting collaborative learning in mathematics education within school environments, using a Systematic Literature Review approach. The literature sources were derived from indexes such as Scopus, DOAJ, Google, and Google Scholar, with a focus on publications from 2014 to 2024. The findings indicate that cloud computing technology significantly enhances student interaction, personalizes learning, and improves student engagement and academic outcomes. Tools and platforms like SageMathCloud, Google Drive, and cloud-based LMS have proven effective in facilitating collaboration, resource sharing, and creating dynamic, interactive learning environments. Additionally, the integration of Information and Communication Technology (ICT) in STEM education, including the use of programming and robotics, provides opportunities to develop critical thinking and problem-solving skills, which are essential in contemporary mathematics education. This study highlights the significant potential of cloud computing technology to improve mathematics learning outcomes across various educational levels